Percepção da qualidade de vida de idosas participantes e não participantes de um grupo de convivência da terceira idade de Catanduva (SP) - Braz, Igor Augusto (2012)
Introduction: The change in the Brazilian demographic layer has caused several changes in the lifestyle of individuals. The morbidity caused by the aging process have led elderly over 60 years old to seek new alternatives to improving their quality of life. An important strategy used in promoting the health of the elderly are the living groups for seniors that offers activities taught by professionals from various fields. These groups provide health benefits for participants and are gaining more women's followers. Objectives: The aim of this study was to compare the perceived quality of life among elderly participants and non-participants of a group of senior citizens living in the city of Catanduva (SP). Materials and Methods: Sixty elderly women voluntarily participated in this study (≥ 60 years old) who formed two groups. The first group was composed of elderly participants living group of seniors in the city of Catanduva (SP) and the second group consisting of older who were part of the social context of the women of the first group but they had never participated in a support group. The perceived quality of life questionnaires WHOQOL-BREF and WHOQOLold were applied in groups as well as a questionnaire with objective to profile sociodemographic groups. Results: The elderly participants of living group showed significantly higher values in all domains of the WHOQOL-BREF and the facets of sensorimotor functioning, activities past, present and future, social participation and intimacy of the questionnaire WHOQOL-old. Similarly the education level and frequency of weekly physical activity reported by elderly participants of living group showed statistically higher values. The average age of the groups showed no significant difference.